Reconstruction of Human Resource Management in the Era of Disruption in the Study of Islamic Education - Hanapia, Cepi; Purwanto, Purwanto; Rahmatulloh, Aang; Muliasutisna, Asep; Indriani, Lisna (Universitas Pahlawan Tuanku Tambusai, 2025)
The disruption era requires an inclusive and comprehensive observation and research, especially in the world of education in Indonesia. God created humans as caliphs (God's representatives) on earth. Therefore, God gives something that can be seen by humans, heard by humans, felt by humans, and made by humans with the concept of thinking according to the teachings of Alquran. The Word of God, I sent Alqur'an down to the earth for people who want to think (have sense/faith). The famous French philosopher, Descartes said,